2021
DOI: 10.3390/ijerph18115927
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Evaluation of Young People’s, Parents’ and Carers’ Experiences of a National and Specialist CAMHS Dialectical Behaviour Therapy Outpatient Service

Abstract: (1) Background: Dialectical Behaviour Therapy (DBT) is the recommended treatment for Borderline Personality Disorder (BPD) symptoms in adults, however, research investigating the effectiveness of DBT for adolescents is limited. The present study explores the experiences of young people and their parents/carers of a DBT service using qualitative methodology. (2) Methods: Young people and their parents/carers, who completed DBT within the National and Specialist Child and Adolescent Mental Health DBT Service bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…37 Few papers have been published since this review 38 and the majority focus on small samples of speci c populations. 39,40 However, although quantitative ndings are crucial for evaluating a therapy's e cacy, the qualitative investigation of client experience can provide invaluable insight for re ning a therapy's model and delivery. 41 Qualitative research permits an in-depth understanding of processes and phenomena 42 and can thus detail helpful or unhelpful aspects of a therapy in a way that quantitative measures may not be able to.…”
Section: Client Experiences Of Dbtmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Few papers have been published since this review 38 and the majority focus on small samples of speci c populations. 39,40 However, although quantitative ndings are crucial for evaluating a therapy's e cacy, the qualitative investigation of client experience can provide invaluable insight for re ning a therapy's model and delivery. 41 Qualitative research permits an in-depth understanding of processes and phenomena 42 and can thus detail helpful or unhelpful aspects of a therapy in a way that quantitative measures may not be able to.…”
Section: Client Experiences Of Dbtmentioning
confidence: 99%
“…Due to the value of qualitative investigation, there is a well-endorsed recent trend in therapeutic research toward the integration of quantitative and qualitative methodologies. 43 However, given the paucity of qualitative data on the topic at hand, there is a current call in the literature to increase the available data for the client experience of DBT 39 and therefore facilitate any effective adaptations in the delivery of the therapy that may be required.…”
Section: Client Experiences Of Dbtmentioning
confidence: 99%
“…The service experiences of young people and their parents/carers who completed Dialectical Behaviour Therapy (DBT) treatment in the UK were explored by Ratnaweera and co-authors [ 12 ]. Young people indicated that the treatment program was experienced as a person-centred approach, and resulted in a new way of living, better self-understanding, and the acquisition of new skills.…”
Section: The Special Issuementioning
confidence: 99%
“…The approach also helps them to report more positive interactions with their parents and strengthens their general sense of well-being (Neece, 2014; Neece et al, 2013; Pardo et al, 2020). Although DBT was designed for adults in the beginning, DBT-A has been shown to be a particularly competent therapeutic approach for adolescents with a tendency toward self-harm (Chugani et al, 2021; Fleischhaker et al, 2011; Kothgassner et al, 2021; Ratnaweera et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing the success of DBT in the population with BPD and deliberate self-harm, researchers have for some time suggested that DBT may be an efficient approach for other disorders involving emotional problems (Neacsiu et al, 2013; Ratnaweera et al, 2021). With this in mind, studies have focused on the use of DBT to treat diagnoses such as depressive disorder and anxiety (Saito et al, 2020).…”
Section: Introductionmentioning
confidence: 99%